The role of public authorities in corporate social responsibility - Semenescu, Andreea; Badarau, Cristina (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2014)
We analyze the possible responses of public authorities to corporate socially responsible initiatives and the effects on the corporate decision of undertaking socially responsible investments. We shed light on the interference of public and private decisions regarding corporate socially responsible investment and on the manner it affects the expected outcomes. The influence of public authorities on corporate social responsibility decisions is complex. First, we explain the failure of public services as the motivation for socially responsible actions undertaken by companies. Second, we deal with the response of public authorities to corporate responsible investment. Public authorities may adopt cooperative or non-cooperative behavior that affects the equilibrium reached in the market. Their choice influences the decision of the company to develop socially responsible projects. We exemplify by a simple model the microeconomic insights of corporate social responsibility decisions. The study can be useful as a start point in the capital budgeting of this type of investment. It also offers a new perspective showing how corporate social responsibility can become an instrument for improving market equilibrium
Argumenta Oeconomica, 2014, Nr 2 (33), s. 39-66
Keywords: corporate social responsibility; Pareto improving; second best; corporate regulation; privately provided public goods